Using Kharrat-Toma transform to solve a growth and decay problem - Rebaz; Siyaman Sidiq Hama; Shwan Swara Fatah; Hozan Hilmi (Tikrit Journal of Pure Science, 2024)
Many academics have recently concentrated on applying integral transforms to solve challenging problems in economics, biology, engineering, and medicine. In this paper, the Kharrat-Toma transform is used to issues related to population growth and decay problem. These are important topics in the fields of finance, physics, chemistry, biology, and society. Many applications show the value and efficacy the Kharrat-Toma transform is used to analyze concerns with population growth and decrease. The findings demonstrate the usefulness of the Kharrat-Toma transform in resolving problems associated with population growth and deterioration. In population growth and decay problems there is a differential equation model in mathematics that can be analyzed by the Kharat-Toma transform. We have shown its analysis and applications in this article.